Spastic paraplegia type 31: A novel REEP1 splice site donor variant and expansion of the phenotype variability. (January 2018) - Kamada, Masaki; Kawarai, Toshitaka; Miyamoto, Ryosuke; Kawakita, Rie; Tojima, Yuki; Montecchiani, Celeste; D'Onofrio, Laura; Caltagirone, Carlo; Orlacchio, Antonio; Kaji, Ryuji
Abstract: Mutations in REEP1 have been identified in three types of neurological disorders, autosomal dominant form of Hereditary Spastic Paraplegia type 31 (SPG31), autosomal dominant distal hereditary motor neuronopathy type VB (HMN5B), and autosomal recessive form of congenital axonal neuropathy and diaphragmatic palsy. Previous studies demonstrated different molecular pathogenesis in SPG31, including loss-of-function, gain-of-function and haploinsufficiency. A four-generation family from Japan, including 12 members, was investigated clinically and genetically. Seven affected members displayed pure spastic paraplegia. Impression of genetic anticipation was observed in the family, including tendency of earlier age-at-onset and increasing severity in subsequent generations. Genetic analysis revealed a heterozygous intronic variant, c.303+2T > A, in REEP1, which segregated with disease, and was also identified in one unaffected member. The variant causes exon 4 skipping leading to frame shift and a truncated transcript identified by complementary DNA sequencing of reverse transcription polymerase chain reaction products. Measurement of REEP1 transcripts in lymphocytes demonstrated a reduction through nonsense mediated mRNA decay (NMD). Our study demonstrated further evidence of allelic heterogeneity in SPG31, mutant REEP1 mRNA dosage effects through NMD and intra-familial phenotype variability. Graphical abstract: Highlights: A novel REEP1 splice site donor variant was demonstrated in a Japanese family with spastic paraplegia. The intronic variant results in skipping of exon 4 and creates a premature termination. Aberrant REEP1 transcripts were subjected to nonsense-mediated mRNA decay. Phenotypic variability was shown, including asymptomatic carrier and possible genetic anticipation. Pathology of SPG31 may contain dosage effect of REEP1 transcripts and other genetic factor(s).